2017
DOI: 10.3389/fcimb.2017.00414
|View full text |Cite
|
Sign up to set email alerts
|

Aspartic Proteases and Major Cell Wall Components in Candida albicans Trigger the Release of Neutrophil Extracellular Traps

Abstract: Neutrophils use different mechanisms to cope with pathogens that invade the host organism. The most intriguing of these responses is a release of neutrophil extracellular traps (NETs) composed of decondensed chromatin and granular proteins with antimicrobial activity. An important potential target of NETs is Candida albicans—an opportunistic fungal pathogen that employs morphological and phenotype switches and biofilm formation during contact with neutrophils, accompanied by changes in epitope exposition that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 108 publications
3
85
1
Order By: Relevance
“…Neutrophil adhesion to endothelial cells. Human polymorphonuclear cells (PMN) were isolated as described previously (Zawrotniak et al, 2017) from freshly EDTA-treated whole-blood samples obtained from the Regional Blood Donation Center (Krakow, Poland), which complies with the requisite of confidentiality assurance for human participants. Isolated PMN were suspended in RPMI-1640 medium and loaded with Cell Tracker Red CMTPX in RPMI for 30 min at 37°C, following the manufacturer's instructions, and then placed on a monolayer of endothelial cells stimulated as described below.…”
Section: Methodsmentioning
confidence: 99%
“…Neutrophil adhesion to endothelial cells. Human polymorphonuclear cells (PMN) were isolated as described previously (Zawrotniak et al, 2017) from freshly EDTA-treated whole-blood samples obtained from the Regional Blood Donation Center (Krakow, Poland), which complies with the requisite of confidentiality assurance for human participants. Isolated PMN were suspended in RPMI-1640 medium and loaded with Cell Tracker Red CMTPX in RPMI for 30 min at 37°C, following the manufacturer's instructions, and then placed on a monolayer of endothelial cells stimulated as described below.…”
Section: Methodsmentioning
confidence: 99%
“…). Recently, we found that SAP genes are overexpressed in yeast during contact with NET‐forming neutrophils and that Saps can trigger NET release …”
Section: Sap Functions In Candidal Virulence and Host‐pathogen Interamentioning
confidence: 99%
“…Recently, we found that SAP genes are overexpressed in yeast during contact with NET-forming neutrophils 87 and that Saps can trigger NET release. 120 Candida albicans extracellular proteinases can induce the expression of cytokines in host immune cells. In macrophages, Sap1-Sap3…”
Section: Interactions With Host Defense Cellsmentioning
confidence: 99%
“…Such an argument was also strengthened by the observation that pre-treatment of PMNs with interferon-γ or granulocyte colony-stimulating factor (G-CSF) did not significantly enhance their activity against opsonized or nonopsonized C. albicans biofilms. Moreover, neutrophils contacting the mature biofilm did not produce reactive oxygen species, necessary for triggering of phagocytosis, or one of the pathways of NET production [99]. Nevertheless, the precise mechanism of this phenomenon remained to be clarified.…”
Section: Host Responses To the Candidal Biofilmsmentioning
confidence: 98%